Settlement of Default Disputes in Credit Agreements between Banks BPR (BUMD BIMA) and Customers Using State Attorneys - Apriani, Uni (International Significance of Notary, 2024)
Abstract : The State Attorney is a government apparatus that acts in law enforcement in accordance with Law Number 11 of 2021 concerning Amendments to Law Number 16 of 2004. The problems raised by the author are to determine the Settlement of Default Disputes in Credit Agreements Between BPR Banks (BUMD BIMA) ) With Customers Who Use State Attorneys (Studies At the Coastal Bank of Bima City). The research method uses sociological juridical in the form of interviews conducted by the author directly. Based on the results of the study that in its duties and authorities the State Attorney's Attorney has a very important role in law enforcement, however regarding the above provisions, namely Law Number 11 of 2021 concerning the Indonesian Prosecutor's Office, if what is discussed is related to non-litigation settlement of default disputes, then these rules has not been able to accommodate comprehensively related to mediation efforts carried out by JPN, as stipulated in the Law. For this reason, additional rules are needed, namely the provisions contained in the Decree of the Attorney General of the Republic of Indonesia No: Kep.225/A/J/A/3/2003 Regarding Duties and Authority of State Attorney.Keywords : Duties, Roles, ProsecutorE